More than scales and tape measures needed to address obesity in South Africa - R. Ramlal; R. D. Govender (South African Family Practice)
Obesity is an emerging public health problem worldwide increasing from 857 million in 1980 to 2.1 billion by 2013. A study was done on a sample of 100 obese and overweight patients with a body mass index (BMI) above 25 kg/m2. The patients were asked to complete a questionnaire, which included socio-demographic data and perceptions regarding their weight.